Penerapan Permainan Menulis Tegak Menulis Ejaan (MTME) Untuk Meningkatkan Keterampilan Menulis Siswa Kelas II SDN Darangdan - Resmiadewi, Noviani; Sunarya, Dede Tatang; Djuanda, Dadan (Jurnal Pena Ilmiah, 2019)
The.problem that arises in the process of learning to write the beginning of cursive writing is not in accordance with the shape and size of the.letters and the use of spelling in sentences that are still low. Efforts were.made to improve the learning process and results by applying the Erect Writing Spelling,Writing Application using.striped,cardboard,and color markers. The method used in this study is Action,Research.Class method, with the format of the instrument observing teacher performance and student activities, interviews, questions, and field notes. The subjects of the study were 20 second grade,students of SDN.Darangdan. Based,on the results of the implementation.of three cycles,there was an increase,in the achievement,of indicators. Thus, Developing a.Writing Spelling Cursive Game can,improve.the learning,process and learning outcomes of class II students at SDN Darangdan on,writing cursive,material based on the correct spelling.